1995
DOI: 10.1177/0146167295211007
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and the Prediction of Behavior: A Meta-Analysis of the Empirical Literature

Abstract: The relationship between attitudes and behavior has been the topic of considerable debate. This article reports a meta-analysis of 88 attitude-behavior studies that reveals that attitudes significantly and substantially predict future behavior (mean r = .38; combined p <<. 000000000001). Relatively large and significant moderating effects were found for the attitudinal variables of attitude certainty, stability, accessibility, affective-cognitive consistency, and direct experience (mean q = .39). A small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
866
5
42

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,370 publications
(966 citation statements)
references
References 132 publications
53
866
5
42
Order By: Relevance
“…Ajzen and Fishbein (1977) theorized and showed that attitude-behavior connections were strongest when the attitude was matched in specificity or generality to behavior. More recently, Kraus (1995) also found support for the compatibility principle in nonwork contexts, with meta-analytic correlations (r's) of .29 versus .62 under low and high compatibility, respectively.…”
Section: Connecting Attitudinal Predictors To Behavioral Criteria Thementioning
confidence: 86%
“…Ajzen and Fishbein (1977) theorized and showed that attitude-behavior connections were strongest when the attitude was matched in specificity or generality to behavior. More recently, Kraus (1995) also found support for the compatibility principle in nonwork contexts, with meta-analytic correlations (r's) of .29 versus .62 under low and high compatibility, respectively.…”
Section: Connecting Attitudinal Predictors To Behavioral Criteria Thementioning
confidence: 86%
“…However, the exact relationship between the structural changes and development of the brain and behavioural changes has not been established. It has also been argued that students differ from nonstudents as they are more homogeneous (Calder et al, 1981;Greenberg, 1987;Kraus, 1995). This may result in stronger effect sizes of hypothesis tests than if nonstudents were involved, as there are fewer extraneous variables to be controlled.…”
Section: Use Of Appropriate Samplesmentioning
confidence: 99%
“…The potentially greater homogeneity of the student sample (Calder et al, 1981;Greenberg, 1987;Kraus, 1995;Peterson, 2001), familiarity with completing experiments and questionnaires, and desire to confirm the research hypotheses (Orne, 1962) was expected to lead to more significant results and greater observed effect sizes for students as compared to nonstudents. Furthermore, students' familiarity with completing surveys and elaborating on written responses, and hope to contribute towards science was expected to result in a greater level of detail in written responses than non students participating in gambling venues.…”
Section: Use Of Appropriate Samplesmentioning
confidence: 99%
“…In a meta-analysis of eighty-eight attitude-behaviour studies Kraus (1995) found attitudes significantly and substantially predict future behaviour. However, the majority of studies investigating the relationship between attitudes and behaviour conclude that the direct correlations of attitudes and behaviour are not high (Bagozzi 1978;Bagozzi and Burnkraut 1979;Bruvold 1973;Schuman and Johnson 1976).…”
Section: The Effect Of Attitudes Social Norms and Perceived Behavioumentioning
confidence: 99%